2020
DOI: 10.1039/d0ta02502j
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of configurational flexibility in facilitating reversible reactive metal deposition from borohydride solutions

Abstract: The size-dependent coordination tendencies of metal dications determine their relative abilities to form associated ionic clusters and thus their relative performance in multivalent battery electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
128
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(145 citation statements)
references
References 57 publications
17
128
0
Order By: Relevance
“…Only a few papers are devoted to electrodeposition of yttrium from ILs. Glukhov Calcium electrochemistry in non-aqueous solutions is considered mainly in context of Ca-ion batteries [58,59]. To the best of our knowledge, only one article is directly devoted to electrodeposition of calcium in ILs.…”
Section: Scandium (Sc) and Yttrium (Y)mentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few papers are devoted to electrodeposition of yttrium from ILs. Glukhov Calcium electrochemistry in non-aqueous solutions is considered mainly in context of Ca-ion batteries [58,59]. To the best of our knowledge, only one article is directly devoted to electrodeposition of calcium in ILs.…”
Section: Scandium (Sc) and Yttrium (Y)mentioning
confidence: 99%
“…As a promising materials NiSe or CoSe are considered suitable [95]. Although both metals can be activated in proton flux, generated isotopes have suitable half-lives, 59 Ni (T 1/2 = 76,000 years), 58 Co (T 1/2 = 23.7 min). Ellison et al [95] reported application of CoSe for production of 76,77,80m Br.…”
Section: Selenium (Se)mentioning
confidence: 99%
“…To make electric vehicles feasible, it is imperative to understand considerably new battery chemistries with higher energy densities than the lithium ion, designated as “beyond lithium‐ion” batteries. [ 2,4–8 ] Examples include Li‐air, [ 9 ] Li‐S, [ 10,11 ] Na‐ion [ 12–16 ] batteries, and multivalent‐ion batteries including Mg‐ion, [ 17–38 ] Zn‐ion, [ 39,40 ] and Ca‐ion batteries. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…This article is intended to provide a succinct overview of the recent development of in situ/operando X‐ray spectroscopy and its application in the fundamental and applied research of beyond lithium‐ion batteries. A summary of in situ/operando XAS on various beyond lithium‐ion batteries, including Mg‐ion, [ 17–38 ] Zn‐ion, [ 39,40 ] Ca‐ion, [ 17 ] Li‐S, [ 10,11 ] and Na‐ion [ 12–16 ] batteries, will be discussed in the next section, followed by a brief presentation of several papers employed RIXS and scanning transmission X‐ray microscopy (STXM) for applications in the beyond lithium‐ion battery field. In addition, a perspective on the future problems to solve with the assistance of in situ/operando soft X‐ray spectroscopies will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been found that in the Ca(BH 4 ) 2 /tetrahydrofuran electrolyte, the SEI layer is composed entirely of CaH 2 , granting 95% coulombic efficiency of calcium plating and stripping. [18][19][20] However, CaH 2 is highly reactive, and the formation of CaH 2 passivation layer requires additional electrochemical purification of the electrolyte and a rather clean glovebox atmosphere.…”
Section: Introductionmentioning
confidence: 99%